2019
DOI: 10.1177/0963689719854342
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Grafts of Human Amniotic Fluid-Derived Stem Cells Reduce Behavioral Deficits in Experimental Ischemic Stroke

Abstract: Amniotic fluid has been investigated as new cell source for stem cells in the development of future cell-based transplantation. This study reports isolation of viable human amniotic fluid-derived stem cells, labeled with multimodal iron oxide nanoparticles, and its effect on focal cerebral ischemia–reperfusion injury in Wistar rats. Middle cerebral artery occlusion of 60 min followed by reperfusion for 1 h, 6 h, and 24 h was employed in the present study to produce ischemia and reperfusion-induced cerebral inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…Fifth, we did not perform any type of immunosuppressive study. Our study and previous studies have revealed that injection of hAFSCs in animal models developed no immune rejection against transplanted tissue 17,45,46 . Mesenchymal stem cells have the advantage of immunomodulatory properties, making these cells good candidates for xenotransplantation 47 .…”
Section: Discussionsupporting
confidence: 69%
“…Fifth, we did not perform any type of immunosuppressive study. Our study and previous studies have revealed that injection of hAFSCs in animal models developed no immune rejection against transplanted tissue 17,45,46 . Mesenchymal stem cells have the advantage of immunomodulatory properties, making these cells good candidates for xenotransplantation 47 .…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have shown that human stem cells can improve ischemic outcomes in preclinical animal models [ 36 , 66 , 67 ]. In fact, reports of the immunomodulatory effects and low immunogenicity of human placental derived stem cells (hPMSC) found these cells to be useful candidates for allogenic transplantation and clinical application in regenerative medicine [68] . Therefore, if these cells were effective in animal models, it is likely they could have benefits in human clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…to share similar characteristics to MSCs, including immune modulations, so hAFSCs may not exhibit immune rejection, unlike hematopoietic stem cells. 14,16,22 It is likely that hAFSCs can differentiate and integrate into nervous tissue and have therapeutic potential in treating neurological disorders such as stroke and its complications. Our previous study on bladder dysfunction demonstrated that hAFSCs contribute to help recovery of bladder function in spinal cord injured rats and MCAO rats.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with hAFSCs may facilitate functional recovery in a rodent stroke model. 22 In 60-minute MCAO rats, hAFSCs labelled with iron nanoparticles were found to migrate to the ischaemic region after intravenous transplantation. 22 Transplanted cells may provide support for cell surviving in penumbra area, offer protection from the toxic environment surrounding injured region and stimulate endogenous repair mechanisms such as neurogenesis, angiogenesis and immunomodulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation